2010
DOI: 10.1186/1471-2407-10-662
|View full text |Cite
|
Sign up to set email alerts
|

Specific genomic aberrations in primary colorectal cancer are associated with liver metastases

Abstract: BackgroundAccurate staging of colorectal cancer (CRC) with clinicopathological parameters is important for predicting prognosis and guiding treatment but provides no information about organ site of metastases. Patterns of genomic aberrations in primary colorectal tumors may reveal a chromosomal signature for organ specific metastases.MethodsArray Comparative Genomic Hybridization (aCGH) was employed to asses DNA copy number changes in primary colorectal tumors of three distinctive patient groups. This included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…Furthermore, in our recent work we showed that an amplification of chromosome 20q is strongly related with the development of liver metastases (Bruin et al , 2010). …”
mentioning
confidence: 98%
“…Furthermore, in our recent work we showed that an amplification of chromosome 20q is strongly related with the development of liver metastases (Bruin et al , 2010). …”
mentioning
confidence: 98%
“…For rectal cancer in particular, gene expression profiling has been used to identify a gene signature of local recurrence after chemoradiation therapy, but, for reasons described previously, there is no colon cancer comparison in this study (12). In addition, gene expression profiling has led to the identification of biomarkers related to colorectal cancer staging, metastatic behavior, and clinical response, but these studies typically have not evaluated colon cancer and rectal cancer separately (13)(14)(15). For studies in which data are available for anatomic location, there are significant differences in mRNA and miRNA expression between colon cancers and rectal cancers (15,16).…”
Section: Epigenetic and Genetic Distinctions Between Colon And Rectalmentioning
confidence: 99%
“…[ 33 ] One study that analyzed CNAs between patients with different metastatic patterns showed that gain of the 20q chromosomal arm was associated with liver-specific metastases, suggesting a role in the process of liver metastasis in CRC. [ 34 ] Patients who did not develop metastatic disease and patients with peritoneal metastases showed a gain of 20q less frequently. [ 34 , 35 ] These findings fit very well with the aberrant metastatic pattern that has been observed in MC patients.…”
Section: Discussionmentioning
confidence: 99%